Carer and staff perceptions of end-of-life care provision: case of a hospice-at-home service. (2nd January 2021) - Ward, Alison; Sixsmith, Judith; Spiro, Stephen; Graham, Anne; Ballard, Heather; Varvel, Sue; Youell, Jane
Abstract : People requiring palliative care should have their needs met by services acting in accordance with their wishes. A hospice in the south of England provides such care via a 24/7 hospice at home service. This study aimed to establish how a nurse-led night service supported patients and family carers to remain at home and avoid hospital admissions. Semi-structured interviews were carried out with family carers (n=38) and hospice-at-home staff (n=9). Through night-time phone calls and visits, family carers felt supported by specialist hospice staff whereby only appropriate hospital admission was facilitated. Staff provided mediation between family carer and other services enabling more integrated care and support to remain at home. A hospice-at-home night service can prevent unnecessary hospital admissions and meet patient wishes through specialist care at home.